Avaliação dos efeitos do extrato hidroalcoólico das folhas de erva-de-passarinho (Tripodanthus acutifolius) em ratos wistar hipercolesterolêmicos - Coelho, Ritiéle Pinto (2017)
Cardiovascular diseases (CVD) represent a public health problem, and dyslipidemias are important risk factors for their onset. Changes in the levels of circulating lipids constitute the major impact factor in the development of atherosclerotic disease. According to phytochemical research, it is known that Tripodanthus acutifolius (TA) shows promising antioxidant activity, and has been applied as a hypoglycemic, antibacterial, anti-inflammatory and diuretic compound. Studies indicate that oxidative stress (OE) is directly related to dyslipidemia, playing a prominent role in inflammatory processes and in the progression of atherosclerosis. Thus, the aim of the present study was to evaluate the effects of hydroalcoholic Tripodanthus acutifolius leaf extracts on hypercholesterolemic Wistar rats. The animals were divided into 5 groups: NC (Normocaloric Control); HC (Hypercaloric Control); Oral Simvastatin Suspension 10 mg/kg (SIM 10 mg/kg); TA Extract 50 mg/kg (TA 50 mg/kg) and TA Extract 100 mg/kg (TA 100 mg/kg). The NC group was the only one to receive only feed, while the others received a hypercholesterolemic diet for 30 days. After hypercholesterolemia confirmation, the formulations were administered by gavage once a day. Rats were then euthanized and venous blood and organs were collected for further analyses. The phytochemical analysis of the lyophilized TA powder leaves was performed by HPLC-DAD. The major compound found in the TA leaves was isoquercitrin, followed by catechin and luteolin. In vitro assays were performed to determine antioxidant activity. The TA extract (0.5 mg/mL) resulted in 95.3% DPPH inhibition and 92.40% ABTS inhibition. Total polyphenols showed a dose-dependent behavior. At 1.0 mg/mL, total phenolic concentrations showed 45.80 mg gallic acid mL-1. In vivo assays demonstrated that all TA-supplemented groups showed a significant (p <0.05) decrease in total platelet counts relative to the control groups. In addition, the HC and SIM groups showed high monocyte counts when compared to the TA-supplemented groups. A significant (p <0.05) decrease in total ix cholesterol levels was observed in all TA-supplemented groups compared to HC, with lower levels than even the NC group. A significant (p <0.05) decrease in triglycerides and LDL-cholesterol levels in all TA-treated groups was also observed, as well as increases in HDL cholesterol levels compared to the HC group. Significant decreases (p <0.05) in liver, renal and cardiac function markers were observed after TA treatment. The analysis of inflammatory markers revealed a significant increase (p <0.05) in adiponectin and decrease in PCRus levels in the TA-supplemented groups in relation to the HC group. The TA-supplemented groups also showed a significant decrease (p <0.05) in relation to HC in lipid peroxidation, protein carbonylation and micronucleus frequency induced by hypercholesterolemia, as well as a significant increase (p <0.05) in the activity of the antioxidant enzymes CAT, SOD and GPx and an increase in Polyphenols, Vit C and GSH. The histological analysis demonstrated that the treatment was able to reduce aortic spasm, exhibiting a protective effect against atherosclerosis. Thus, it may be suggested that TA extract is promising in the treatment of dyslipidemia.